Evaluation of sewage sludge biochar and modified derivatives as novel SPE adsorbents for monitoring of bisphenol A. (April 2021) - Birer, Ayşe Mulla; Gözmen, Belgin; Sönmez, Özgür; Kalderis, Dimitrios
Abstract: Sewage sludge is abundant biomass, the sustainable management of which remains a big issue worldwide. It was demonstrated that pyrolysis of sewage sludge using simple and cost-effective apparatus can produce biochars, suitable for solid-phase extraction applications of hydrophobic analytes. Detailed characterization showed that modification lead to three more hydrophobic and one more hydrophilic sample, compared to the original biochar. All samples were evaluated in the solid-phase extraction of the emerging contaminant Bisphenol A from aqueous solutions. KOH-SSB and KOH/MeOH-SSB exhibited the most promising behavior, with the latter achieving recoveries of 88.1%, at a quantity of 0.1 g at the natural pH of the BPA solution (6.5). The effect of solution pH was insignificant in the range of 4–7, whereas the initial BPA concentration had no effect in the recovery within the range of 1–100 μg L −1 . The mechanism of interaction between the optimum sample and BPA was based on hydrogen bonding and π-π interactions, establishing earlier observations that the type (and not concentration) of individual surface groups and the total surface area play a significant role in the process. Graphical abstract: Image 1 Highlights: Sewage sludge was used as feedstock for the production of biochar. A cost-effective and safe flame-cap pyrolysis kiln was used for this purpose. The hydrophobic KOH/methanol-modified biochar recovered 88% of BPA at pH 6.5 Hydrogen bonds, π-π interactions and pore-filling formed the interaction mechanism.